Anaphylaxis Refractory to intramuscular adrenaline during in‐hospital food challenges: A case series and proposed management. Issue 12 (25th October 2020) - Alviani, Cherry; Burrell, Sarah; Macleod, Abigail; Edees, Susan; Roberts, Graham; Turner, Paul J; Erlewyn‐Lajeunesse, Michel
Abstract: Background: Anaphylaxis is a severe, systemic hypersensitivity reaction that can be potentially life‐threatening. Anaphylaxis during oral food challenge is not uncommon and can usually be effectively managed with intramuscular adrenaline as first line treatment. Although very rare, fatal anaphylaxis during in‐hospital food challenge has been reported. Objective: We describe our experience of cases of refractory anaphylaxis at in‐hospital challenge and propose a framework for escalation of treatment in such cases using intravenous infusion of adrenaline which has been adopted for widespread use elsewhere. Methods: We present four patients who all experienced severe life‐threatening anaphylaxis, refractory to intramuscular adrenaline treatment, during supervised oral food challenges. Patient data were collected from contemporaneous notes, and patient consent was obtained. Results: In all four cases, the anaphylaxis reactions were amenable to treatment with low‐dose intravenous adrenaline, with no reported adverse effects. Conclusion and clinical relevance: These cases demonstrate the need for clinicians undertaking higher risk allergen challenges to be able to manage cases of severe anaphylaxis refractory to intramuscular adrenaline, and to consider a framework for managing these reactions. While peripheral intravenous adrenaline infusions should always be initiated only in conjunction with expert input, the protocol suggested is simple enough to be undertaken within the hospital environment while more experienced support is obtained.